The C Terminus of Rpt3, an ATPase Subunit of PA700 (19 S) Regulatory Complex, Is Essential for 26 S Proteasome Assembly but Not for Activation - Kumar, Brajesh (American Society for Biochemistry and Molecular Biology, 2010)
PA700, the 19 S regulatory subcomplex of the 26 S proteasome, contains a heterohexameric ring of AAA subunits (Rpt1 to -6) that forms the binding interface with a heteroheptameric ring of α subunits (α1 to -7) of the 20 S proteasome. Binding of these subcomplexes is mediated by interactions of C termini of certain Rpt subunits with cognate binding sites on the 20 S proteasome. Binding of two Rpt subunits (Rpt2 and Rpt5) depends on their last three residues, which share an HbYX motif (where Hb is a hydrophobic amino acid) and open substrate access gates in the center of the α ring. The relative roles of other Rpt subunits for proteasome binding and activation remain poorly understood. Here we demonstrate that the C-terminal HbYX motif of Rpt3 binds to the 20 S proteasome but does not promote proteasome gating. Binding requires the last three residues and occurs at a dedicated site on the proteasome. A C-terminal peptide of Rpt3 blocked ATP-dependent in vitro assembly of 26 S proteasome from PA700 and 20 S proteasome. In HEK293 cells, wild-type Rpt3, but not Rpt3 lacking the HbYX motif was incorporated into 26 S proteasome. These results indicate that the C terminus of Rpt3 was required for cellular assembly of this subunit into 26 S proteasome. Mutant Rpt3 was assembled into intact PA700. This result indicates that intact PA700 can be assembled independently of association with 20 S proteasome and thus may be a direct precursor for 26 S proteasome assembly under normal conditions. These results provide new insights to the non-equivalent roles of Rpt subunits in 26 S proteasome function and identify specific roles for Rpt3.